Through deaf eyes [videorecording (DVD)] - Hott, Lawrence R.; Garey, Diane; Channing, Stockard; Gannon, Jack R.; Caplan, Kimby; Betts, Wayne, Jr; Luhn, Arthur; Mangiardi, Adrean; Salaway, Tracey; Visco, Rene (WETA-TV ; Distributed by PBS Home Video, 2007)
Exploring nearly 200 years of Deaf life in America, this film presents the shared experiences of American history--family life, education, work, and community connections--from the perspective of deaf citizens. Interviews include community leaders, historians, and deaf Americans with diverse views on language use, technology, and identity. The documentary also takes a straightforward look at life for people who are part of the cultural-linguistic group who use American Sign Language and often define themselves as "Deaf" with a capital and cultural "D" and deaf people who, for a variety of reasons, do not identify with the Deaf cultural community. The history often shows that intersections between deaf and Deaf people are many and that oppression and discrimination are common experiences.